Orphan Drugs, Compounded Medication and Pharmaceutical Commons - Hendrickx, Kim; Dooms, Marc (Frontiers in Pharmacology, 2021)
Regulatory agencies installed orphan drug regulations to stimulate research and development of new innovative treatments for life-threatening diseases with a low prevalence. We established a list of well-known food-related ingredients with clinical evidence for rare diseases in the open medical literature that obtained marketing authorization as an expensive “orphan drug”, protected by intellectual property (IP) rights. We show that these ingredients are part of an established practice of medicinal compounding and argue that they should be considered as “pharmaceutical commons”, and that regulatory incentives for private companies and market protection mechanisms such as IP rights are not justified in this case.